Measuring and evaluating ecological flows from streams to regions: Steps towards national coverage. (19th February 2018) - McKenna, James E.; Reeves, Howard W.; Seelbach, Paul W.
Abstract: Living aquatic communities are largely determined and maintained by the volume and quality of flowing waters, both within lotic systems and in receiving waters of coastal systems. However, flow is one of the most frequently and extensively altered features of rivers and streams; alteration effects are likely to be exacerbated by climate change. Lotic systems vary and different fish species need different environmental conditions, and distinct problems are evident at various spatial scales. New synoptic flow and biological information now make it possible to evaluate the effects of altered flows throughout the Great Lakes Region at scales from the stream reach to the Region. We used estimates of river and streamflow and observed fish abundances to develop tools that specify the response of fish to alterations in those flows. We fit the logistic model to a cumulative fish abundance curve as a function of yield providing an empirical means to develop models of the response of cumulative fish abundance to flows. Response zones of yield for each species in each system type (based on size and thermal class) illustrate how criteria may be developed that can be used in decision‐making for management of flows. In our example application, we evaluate both the general response of brook trout ( Salvelinus fontinalis ) abundances (and fish diversity) to changes in flows and assess the sensitivity of each stream fish community to flow alteration. Mapping stream sensitivity to flow alteration throughout the US Great Lakes Region with a multiscale spatial framework showed how regional variability in sensitivity for any fish species or assemblage may be evaluated and provides managers with information to help determine where the best opportunities for protection or restoration of streamflows and associated communities exist. These results provide valuable tools and critical information to managers responsible for balancing water uses and maintaining high quality lotic ecosystems. These methods may be applied to any geographic region and can be extended nationally or globally, where flow, temperature, fish and landscape data are available.